1999
DOI: 10.1063/1.124227
|View full text |Cite
|
Sign up to set email alerts
|

Indium tin oxide contacts to gallium nitride optoelectronic devices

Abstract: We have fabricated GaN-based light-emitting diodes using transparent indium tin oxide (ITO) p contacts. ITO-contacted devices required an additional 2 V to drive 10 mA, as compared to similar devices with metal contacts. However, ITO has lower optical absorption at 420 nm (α=664 cm−1) than commonly used thin metal films (α=3×105 cm−1). Uniform luminescence was observed in ITO-contacted devices, indicating effective hole injection and current spreading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
132
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(135 citation statements)
references
References 13 publications
3
132
0
Order By: Relevance
“…The optical transmission ~75% was measured on 120 nm thick ZnO films. For comparison, to yield the same transmission, the Ni/Au metallization had to be thinned down to ~15 nm [5], while ~80% transmission was reported for 25 nm thick ITO contacts [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optical transmission ~75% was measured on 120 nm thick ZnO films. For comparison, to yield the same transmission, the Ni/Au metallization had to be thinned down to ~15 nm [5], while ~80% transmission was reported for 25 nm thick ITO contacts [6].…”
Section: Discussionmentioning
confidence: 99%
“…Another approach for obtaining effective current-spreading layer, providing low-resistivity contact to p-type GaN in conjunction with efficient and uniform light emission, would be to make the p-type contact/window layer from a transparent conducting oxide (TCO). Following this approach, indium tin oxide (ITO) films have been recently tested as electrical contacts to p-side of GaN-based light emitting diode (LED), vertical cavity laser (VCSEL) and resonant cavity LED, allowing satisfactory lateral current spreading and required transparency [6,7]. Below, we report on the use of ZnO as an ohmic contact to p-GaN.…”
Section: Introductionmentioning
confidence: 99%
“…Although direct contact of ITO on p-GaN shows the Schottky contact behavior [6], enhanced light extraction LEDs has been reported using oxidized Ni/Au-ITO and Ni/ITO contacts with V f (operating voltage) comparable to conventional LEDs [7,8]. In addition, ITO on LED employing a tunnel junction has been investigated and showed superior optical and electrical performance over conventional N 2 -anneled Ni/Au CSL design [9].…”
Section: Introductionmentioning
confidence: 99%
“…12 The dominant TCO is amorphous indium tin oxide (ITO), most commonly deposited by sputtering techniques. [13][14][15][16] Due to the deposition technique and material quality, it has been shown that there is usually a high contact resistance at the p-GaN/ITO interface, and consequently ITO-contacted LEDs exhibited a significantly higher turn-on voltage than that of metalcontacted devices. 13 ZnO has the potential to be a more favorable candidate than ITO in this regard, because the a-axis lattice constant of ZnO is closely matched to that of GaN, and so high-quality ZnO films can be grown epitaxially on GaN.…”
mentioning
confidence: 99%
“…[13][14][15][16] Due to the deposition technique and material quality, it has been shown that there is usually a high contact resistance at the p-GaN/ITO interface, and consequently ITO-contacted LEDs exhibited a significantly higher turn-on voltage than that of metalcontacted devices. 13 ZnO has the potential to be a more favorable candidate than ITO in this regard, because the a-axis lattice constant of ZnO is closely matched to that of GaN, and so high-quality ZnO films can be grown epitaxially on GaN. 17,18 There is also great economical motivation for implementing ZnO as a contact over ITO, as the price of In has been rising and is significantly higher than the price of Zn.…”
mentioning
confidence: 99%